KESAKSIAN ANGGOTA TUBUH DI HARI KIAMAT PERSPEKTIF TAFSIR SAINS - Rizki Pauziah Siregar (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2021)
Testimony is a statement made by a witness who saw the incident by himself and was at the scene at that time. Nothing can escape this evidence in the afterlife, nor can it be manipulated in the slightest. So the source of the problem that will be discussed is how to witness the body and the interpretation of the rationality of the testimony of the limbs in QS. Yasin: 65. The research approach used by the author is a qualitative approach and is more inclined to follow library research and uses thematic analysis methods, this research will rely on the interpretation of Al-Jawahir Fi Tafsiril Qur'an by Tantawi Jauhari and books. as primary sources, research journals, and research theses as secondary sources. And what is relevant to this research, the results of the testimony of the limbs according to tantawi Jauhari are that the limbs will testify and it is not only in the afterlife, the body can testify against its owner. but even in the law that applies in the world, the limb that can be used to prove it, to reveal a crime such as murder or abuse. Here the limbs are like hands, it can help to expose the crime. One of them uses a DNA or fingerprint test, and only Allah will see what the testimony on the Day of Judgment is.